Phosphine-free Suzuki cross-coupling reaction using an efficient and reusable Pd catalyst in an aqueous medium under microwave irradia (2015)
We report here an improved, highly efficient, and general method for the ligand-free Suzuki cross-coupling reaction to the synthesis of biaryls, bipyridyls, thienylpyridine, and allylphenols. Microwave irradiation of (het)aryl halides and (hetaryl, allyl)arylboronic acid N-methyl-iminodiacetic acid (MIDA) ester, using polyurea microencapsulated palladium catalyst (Pd EnCat 30), gave the coupling adducts 1a–x in excellent yields in just 10–18 min.